2012
DOI: 10.1136/flgastro-2011-100056
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of parenteral nutrition-associated cholestasis in an adult using fish oil-based parenteral nutrition

Abstract: Parenteral nutrition-associated cholestasis (PNAC) is a severe complication of parenteral nutrition. Standard feed preparations contain soybean and olive oil that are rich in ω-6 polyunsaturated fats, and which studies suggest can be hepatotoxic. Preparations containing fish oil, rich in ω-3 polyunsaturated fats, may be hepatoprotective and have been used in the critical care setting as immunotherapy. A case demonstrating dramatic improvement in liver function and overall clinical condition in an adult with PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Lisa H Moyes et al reported that PNassociated liver disease in an adult patient resolved after ClinOleic 20% was changed to the SMOF lipid emulsion. 38 Currently, the use of alternative sources of parenteral lipids is an active area of research in the treatment and prevention of cholestasis in preterm infants. We are also currently conducting randomized controlled trial studies to determine the effects of fish oil.…”
Section: Incidence Of Pnacmentioning
confidence: 99%
“…Lisa H Moyes et al reported that PNassociated liver disease in an adult patient resolved after ClinOleic 20% was changed to the SMOF lipid emulsion. 38 Currently, the use of alternative sources of parenteral lipids is an active area of research in the treatment and prevention of cholestasis in preterm infants. We are also currently conducting randomized controlled trial studies to determine the effects of fish oil.…”
Section: Incidence Of Pnacmentioning
confidence: 99%
“…Moyes et al in 2012 reported the devlopment of jaundice in a 43-year old man who had received 6 months of a mixture of refined olive oil (80%) and soybean oil (20%) with the liver biopsy showing severe acute cholestasis, minimal steatosis without inflammation and portal fibrosis all consistent with PNALD [ 73 ]. Subsequently the patient developed portal hypertension which resulted in a gastric variceal bleed.…”
Section: Management Approachesmentioning
confidence: 99%
“…Subsequently the patient developed portal hypertension which resulted in a gastric variceal bleed. A change to SMOFlipid 20% was implemented which provided the patient with a mixture of soybean (30%), medium-chain triglycerides (30%), olive oil (25%) and fish oils (15%) [ 73 ]. Over 16 months of treatment with SMOFlipid20% the patient developed biochemical improvement, resolution of portal hypertension and a decrease in liver stiffness assessed by serial fibroscan [ 73 ].…”
Section: Management Approachesmentioning
confidence: 99%
See 1 more Smart Citation